Power electronics - Gnanavadivel, J (Anuradha Publications, 2011)
The main aim of this book is to provide a basic concepts of power semiconductor devices, single phase controlled rectifiers, there phase controlled rectifiers, DC choppers, inverters, AC-AC converters, control circuits and applications in a lucid way with neat sketches and waveforms. Each chapter contains two mark question dan answers to get complete knowledge of the subject. Large number of worked examples are added to the clarity of the subject matter.